2008
DOI: 10.1029/2007jd009372
|View full text |Cite
|
Sign up to set email alerts
|

Does the Madden‐Julian Oscillation influence aerosol variability?

Abstract: [1] We investigate the modulation of aerosols by the Madden-Julian Oscillation (MJO) using multiple, global satellite aerosol products: aerosol index (AI) from the Total Ozone Mapping Spectrometer (TOMS) on Nimbus-7, and aerosol optical thickness (AOT) from the Moderate Resolution Imaging Spectroradiometer (MODIS) on Terra and Aqua and the Advanced Very High Resolution Radiometer (AVHRR) on NOAA satellites. A composite MJO analysis indicates that large variations in the TOMS AI and MODIS/AVHRR AOT are found ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 104 publications
(161 reference statements)
3
89
0
Order By: Relevance
“…14(a) and (b). For example, the direct application of OMI retrievals to SEA has met with significant difficulty (Tian et al, 2008). Average seasonal optical depths (Fig.…”
Section: Uv Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14(a) and (b). For example, the direct application of OMI retrievals to SEA has met with significant difficulty (Tian et al, 2008). Average seasonal optical depths (Fig.…”
Section: Uv Methodsmentioning
confidence: 99%
“…Subsidence, and consequently negative precipitation anomalies, leads and lags this convective region, with the more dominant subsidence being observed on the eastern side when the convective region is in the Indian Ocean, and on the western side when the convective region is in the Pacific. Thus, from an aerosol point of view, the wet and dry phases of the MJO largely dictate the timing of significant smoke events in the MC (Reid et al, 2012), and the MJO was hypothesized to influence overall AOD (Tian et al, 2008). The amplitude of the MJO is the strongest in boreal winter and early boreal spring with a secondary maximum in boreal summer (Zhang and Dong, 2004).…”
Section: Meteorological Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…From an aerosol point of view, while ENSO is an excellent large-scale indicator of seasonal burning, the wet and dry phases of the MJO strongly influence the intraseasonal timing of significant smoke events in the MC (Reid et al, 2012). While the MJO was hypothesized to influence overall AOT (Tian et al, 2008), no satellite-based AOT verification of this has yet been established due to the difficulty in performing aerosol remote sensing in the region (Reid et al, 2013). However, fire observations are strongly enhanced in dry phases (Reid et al, 2012) and mechanistically a relationship between dry MJO phase, fire emissions, and high AOT seems certain.…”
Section: Evolution Of the Meteorological Environment During The Vascomentioning
confidence: 99%
“…An analysis of aerosol observations from TOMS, AVHRR, and MODIS looked for intra-seasonal variations in AOD over the tropical Pacific and Indian oceans, with inconclusive results due to difficulties in interpreting the satellite products in these regions, namely possible cloud contamination or other ambiguities contributing to the observed patterns (Tian et al, 2008). However, a follow-up study applied the same technique over the tropical Atlantic, and showed that about 25% of the total variance of MODIS AOD can be accounted for by the intra-seasonal variability related to the Madden-Julian Oscillation (MJO) (Tian et al, 2011).…”
Section: Intra-seasonal and Seasonal Variationsmentioning
confidence: 99%